Dynamic routing of wireless electrical sensors based on neural networks - Yamnenko, Ju.; Khokhlov, Yu.; Redko, O. (Технічна електродинаміка, 2016)
A method of dynamic routing based on the operation principles of neural networks, which allows to improve wireless sensor network by using an additional mechanism of error level accounting on routes. This method allows to dynamically monitor the quality of routes and select optimal routes.